The Effects of Mediated Exposure to Ethnic-Political Violence on Middle East Youth’s Subsequent Post-Traumatic Stress Symptoms and Aggressive Behavior - Gvirsman, Shira Dvir (Communic Res, 2013)
This study introduces the concept of chronic (i.e., repeated and cumulative) mediated exposure to political violence and investigates its effects on aggressive behavior and post-traumatic stress (PTS) symptoms in young viewers. Embracing the risk-matrix approach, these effects are studied alongside other childhood risk factors that influence maladjustment. A longitudinal study was conducted on a sample of youth who experience the Israeli-Palestinian conflict firsthand (N = 1,207). As hypothesized, higher levels of chronic mediated exposure were longitudinally related to higher levels of PTS symptoms and aggression at peers independently of exposure to violence in other contexts. In the case of aggressive behavior, structural equation analysis (SEM) analyses suggest that, while it is likely there are causal effects in both directions, the bigger effect is probably for exposure to violence stimulating aggression than for aggression stimulating exposure to violence. Both the longitudinal effects on aggression and PTS symptoms were especially strong among youth who demonstrated initially higher levels of the same type of maladjustment. These results support the conceptualization of the relation between media violence and behaviors as “reciprocally determined” or “downward spirals” and highlight the contribution of the risk-matrix approach to the analysis of childhood maladjustment.